2008
DOI: 10.1007/s00531-007-0293-9
|View full text |Cite
|
Sign up to set email alerts
|

The Enya mounds: a lost mound-drift competition

Abstract: The genesis and evolution of cold-water coral banks along the Northeastern Atlantic margin is known to be influenced by several factors, among which the palaeotopography and nature of the coral settling surface, the presence of bottom currents and sediment supply. In this paper, a case study is presented of the Enya mound cluster, located in the southernmost tip of the Belgica mound province, west of Ireland. Below this mound cluster, seismic stratigraphy revealed a yet unmapped local unconformity RD1b, being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
0
25
1
Order By: Relevance
“…A). The linear troughs flanking the seamount (SM) are directly comparable in dimension, cross‐section and planform with erosional/depositional features or ‘moats’ that are commonly documented in bottom current regimes where there is an influence of topography, along topographic highs, such as ridges, banks and islands worldwide (e.g. Faugères et al ., ; Knutz & Cartwright, ; Laberg et al ., ; Surlyk & Lykke‐Andersen, ; Hernández‐Molina et al ., ; Van Rooij et al ., ; Faugères & Mulder, ). Similar erosional troughs formed by bottom currents are also documented in many present and ancient continental margins, such as in the Gulf of Cadiz (Hernández‐Molina et al ., ), the Faeroe‐Shetland gateway (Knutz & Cartwright, ), the Northwest Sub‐Basin of the South China Sea (SCS) (Chen et al ., ) and the Pearl River Mouth Basin of the northern SCS (Sun et al ., ). The elliptical and crescentic mega‐pockmarks in the adjacent area also indicate that strong bottom currents occur in the study area (Sun et al ., ) by analogy with similar structures, such as in the Inner Oslofjord, Norway (Hammer et al ., ), and Adriatic Margin (Verdicchio & Trincardi, ).…”
Section: Discussionmentioning
confidence: 99%
“…A). The linear troughs flanking the seamount (SM) are directly comparable in dimension, cross‐section and planform with erosional/depositional features or ‘moats’ that are commonly documented in bottom current regimes where there is an influence of topography, along topographic highs, such as ridges, banks and islands worldwide (e.g. Faugères et al ., ; Knutz & Cartwright, ; Laberg et al ., ; Surlyk & Lykke‐Andersen, ; Hernández‐Molina et al ., ; Van Rooij et al ., ; Faugères & Mulder, ). Similar erosional troughs formed by bottom currents are also documented in many present and ancient continental margins, such as in the Gulf of Cadiz (Hernández‐Molina et al ., ), the Faeroe‐Shetland gateway (Knutz & Cartwright, ), the Northwest Sub‐Basin of the South China Sea (SCS) (Chen et al ., ) and the Pearl River Mouth Basin of the northern SCS (Sun et al ., ). The elliptical and crescentic mega‐pockmarks in the adjacent area also indicate that strong bottom currents occur in the study area (Sun et al ., ) by analogy with similar structures, such as in the Inner Oslofjord, Norway (Hammer et al ., ), and Adriatic Margin (Verdicchio & Trincardi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the Porcupine Seabight numerous mound provinces exist, in which mounds vary in size up to giant mounds of up to 160 m high and up to 5 km in length: Hovland mounds, Magellan mounds and the Belgica mounds ( De Mol et al, 2002, Hovland et al, 1994, Huvenne et al, 2009a, Van Rooij et al, 2009and Wheeler et al, 2007. The process of accretion of these large mounds is not well understood although coring through the Challenger Mound by IODP Expedition 307 revealed gradual reef stacking over the course of 2.6 Ma.…”
Section: Introductionmentioning
confidence: 99%
“…The complex palaeotopography of the Porcupine Seabight slope (Van Rooij et al, 2007) may have contributed to enhance the tidally modulated bottom currents, driving the formation of a complex CDS in close association with the CWC mounds. However, the existence of a large erosional unconformity RD1, acting as the base of the Belgica CWC mounds, regionally represents large hiatuses (from 6.6 to 8.2 Myr) and was possibly created by several incision phases (Kano et al, 2007;Louwye et al, 2008;Van Rooij et al, 2009). The sedimentation first resumed in the form of CWC mound accretion at~2.7 Ma and lagged in off-mound setting, from about 1.24 Ma at site U1318 to about 0.5 Ma depending on the local morphology (Kano et al, 2007;Huvenne et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…During the present day, it has been shown that the strong bottom currents in the eastern Porcupine Seabight are due to internal waves of tidal period (i.e. internal tides) at the upper interface between the MOW and the Eastern North Atlantic Water (White, 2007;Van Rooij et al, 2009). The complex palaeotopography of the Porcupine Seabight slope (Van Rooij et al, 2007) may have contributed to enhance the tidally modulated bottom currents, driving the formation of a complex CDS in close association with the CWC mounds.…”
Section: Introductionmentioning
confidence: 99%